Preparation and Characterization of Mucoadhesive Tablets Containing Nystatin for Treatment of Oral Candidiasis - Fatemeh Ahmadi; Mehdi Alishiri; Zahra Sobhani (Fasa University of Medical Sciences, 2020)
Background & Objective: Nystatin is an antifungal antibiotic commonly used for treatment of candidiasis and widely used against oral mycosis. However, the efficacy of its conventional dosage forms for use in oral cavity is limited by the short residence time and bitter taste of formulation. This research aims to design an optimized formulation of oral mucoadhesive tablets containing nystatin. Therefore, it can be retained in the mouth for long periods and it can cover bitter taste of drug and improve patient's compliance. Materials & methods: The method of tablet preparation was direct compression. Sodium Carboxy Methyl Cellulose, Hydroxy Propyl Methyl Cellulose, Hydroxy Ethyl Cellulose, and Carbopol were used as mucoadhesive polymers. Different types of tablets were formulated using these polymers alone or in combination. The profile of drug released from each tablet was analyzed. The optimum formulation was selected and pharmaceutical analysis and mucoadhesive test were done on it. Results: The optimum mucoadhesive tablet formulation containing nystatin is prepared using sodium Carboxy Methyl Cellulose. In this formulation 70% of nystatin was released in the first 30 min. It has an acceptable mucoadhesive property. Conclusion: Nystatinmucoadhesive tablet containing sodium Carboxy Methyl Cellulose prepared by direct compression method could be used to adhere to the oral mucosa with great appeal and elongation contacting time with localized infection. Therefore, it can lead to the improvemen of the patient's compliance for treatment.